Program Pelatihan Keterampilan Kerja Bagi Pekerja Rumah Tangga Pada Pt Tunas Kreasi Bersama - Dhita Hafizha Asri; Juliyani Juliyani (Universitas Internasional Batam, 2021)
This research was carried out with the aim of analyzing the problems faced by PT Tunas Kreasi Bersama, namely the need to provide development and work skills related to problems that have occurred. The problem faced by the company is the incomplete training of all workers because of the too much capacity of the workers so that not all of them receive training. This practical work activity is from 01 August 2020 - 30 September 2020. Interviews, observations, and simulations are methods used in the implementation of this practical work. Providing training to be more ready and maximized in carrying out actual work practices, the outputs produced from this training are in the form of house keeping, laundry, and family cooking. The implementation stage consists of three stages, namely conducting participant preparation, house keeping training, laundry, and family cooking, getting an assessment from the company which states that the assessment to be added from the implementation results consists of two assessments, namely individual behavior or work attitude and assessment. technical ability.